Early Electroconvulsive Therapy in Patients With Major Depressive Disorder: A Propensity Score-Matched Analysis Using a Nationwide Inpatient Database in Japan. Issue 3 (14th September 2021) - Yamazaki, Ryuichi; Ohbe, Hiroyuki; Matsuda, Yuki; Kito, Shinsuke; Morita, Kojiro; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo
Abstract : Objectives: This study aimed to evaluate whether early electroconvulsive therapy (ECT) can reduce length of hospital stay and total hospitalization costs in major depressive disorder (MDD) patients. Methods: Using the Japanese Diagnosis Procedure Combination inpatient database from April 2011 to March 2018 linked with the Annual Report for Functions of Medical Institutions, we identified patients admitted for MDD. Patients who received ECT within 8 days of admission were assigned to the early ECT group and the remaining patients to the control group. The primary outcomes were length of hospital stay and total hospitalization costs. The secondary outcomes were in-hospital mortality and fatal adverse events. Propensity score-matched analyses were performed to compare the outcomes between the 2 groups. Results: We identified 41, 248 eligible patients, comprising 1169 in the early ECT group and 40, 079 in the control group. After 1:1 propensity score matching, patients in the early ECT group had significantly shorter length of hospital stay than those in the control group (difference: −12.6 days; 95% confidence interval: −17.4 to −7.7 days). There was no significant difference in total hospitalization costs between the 2 groups. Early ECT was not significantly associated with increased in-hospital mortality or fatal adverse events. Conclusions: Early ECT may reduce length of hospital stay without increasing total hospitalization costs or fatal adverse events in patients with MDD.